1994
DOI: 10.1038/369336a0
|View full text |Cite|
|
Sign up to set email alerts
|

Somatostatin-induced inhibition of neuronal Ca2+ current modulated by cGMP-dependent protein kinase

Abstract: Neurotransmitter release is frequently regulated by peptides that modulate neuronal calcium channels. Whole-cell recordings show that the ion permeability and voltage dependence of these channels are controlled by a membrane-associated pathway involving GTP-binding proteins. Here we use perforated-patch recordings to show that, in addition to this pathway, the peptide somatostatin inhibits the calcium current in chick ciliary ganglion neurons by a second soluble pathway involving a cyclic GMP-dependent protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(76 citation statements)
references
References 25 publications
3
69
0
3
Order By: Relevance
“…These studies led to the hypothesis that somatostatin-mediated G protein activation causes a decrease in presynaptic Ca2+ current resulting in decreased ACh release. Electrophysiological recordings from the soma of these neurons in culture confirmed that somatostatin strongly inhibited Ca2+ current in a pertussis toxinsensitive manner (Dryer et al, 1991;Meriney et al, 1994). Furthermore, one of these previous reports implicated a cytoplasmic cyclic GMP (cGMP)-dependent protein kinase (PKG) pathway that altered the characteristics of the membrane-delimited somatostatin-mediated inhibition of Ca2+ current (Meriney et al, 1994).…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…These studies led to the hypothesis that somatostatin-mediated G protein activation causes a decrease in presynaptic Ca2+ current resulting in decreased ACh release. Electrophysiological recordings from the soma of these neurons in culture confirmed that somatostatin strongly inhibited Ca2+ current in a pertussis toxinsensitive manner (Dryer et al, 1991;Meriney et al, 1994). Furthermore, one of these previous reports implicated a cytoplasmic cyclic GMP (cGMP)-dependent protein kinase (PKG) pathway that altered the characteristics of the membrane-delimited somatostatin-mediated inhibition of Ca2+ current (Meriney et al, 1994).…”
mentioning
confidence: 64%
“…Electrophysiological recordings from the soma of these neurons in culture confirmed that somatostatin strongly inhibited Ca2+ current in a pertussis toxinsensitive manner (Dryer et al, 1991;Meriney et al, 1994). Furthermore, one of these previous reports implicated a cytoplasmic cyclic GMP (cGMP)-dependent protein kinase (PKG) pathway that altered the characteristics of the membrane-delimited somatostatin-mediated inhibition of Ca2+ current (Meriney et al, 1994). In this report, we demonstrate that the PKG pathway interacts with the somatostatin-mediated modulation of ACh release from ciliary ganglion neurons and hypothesize that this occurs at a site after Ca2+ entry.…”
mentioning
confidence: 72%
“…As in other systems, it activates a soluble GC (Koch et al, 1994;Ding and Weinberg, 2007) leading to an increase in cGMP production. cGMP is an important regulator of retinal physiology, since it influences a series of biochemical substrates including ion channels (Meriney et al, 1994). It modulates gap…”
Section: Retinal Physiologymentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 17 cGMP-dependent protein kinase (Meriney et al,1994). cGMP was shown to be important in somatostatin's protective actions against NMDA induced neuronal death in cortical cultures (Forloni et al, 1997).…”
Section: No/cgmp As Mediators Of the Neuroprotective Effects Of Somatmentioning
confidence: 99%
See 1 more Smart Citation